Companion Animals Are Spillover Hosts of the Multidrug-Resistant Human Extraintestinal Escherichia coli Pandemic Clones ST131 and ST1193 - Kidsley, Amanda K.; White, Rhys T.; Beatson, Scott A.; Saputra, Sugiyono; Schembri, Mark A.; Gordon, David; Johnson, James R.; O’Dea, Mark; Mollinger, Joanne L.; Abraham, Sam; Trott, Darren J. (Frontiers in Microbiology, 2020)
Escherichia coli sequence types 131 (ST131) and 1193 are multidrug-resistant extraintestinal pathogens that have recently spread epidemically among humans and are occasionally isolated from companion animals. This study characterized a nationwide collection of fluoroquinolone-resistant (FQR) E. coli isolates from extraintestinal infections in Australian cats and dogs. For this, 59 cat and dog FQR clinical E. coli isolates (representing 6.9% of an 855-isolate collection) underwent PCR-based phylotyping and whole-genome sequencing (WGS). Isolates from commensal-associated phylogenetic groups A (14/59, 24%) and B1 (18/59, 31%) were dominant, with ST224 (10/59, 17%), and ST744 (8/59, 14%) predominating. Less prevalent were phylogenetic groups D (12/59, 20%), with ST38 (8/59, 14%) predominating, and virulence-associated phylogenetic group B2 (7/59, 12%), with ST131 predominating (6/7, 86%) and no ST1193 isolates identified. In a WGS-based comparison of 20 cat and dog-source ST131 isolates with 188 reference human and animal ST131 isolates, the cat and dog-source isolates were phylogenetically diverse. Although cat and dog-source ST131 isolates exhibited some minor sub-clustering, most were closely related to human-source ST131 strains. Furthermore, the prevalence of ST131 as a cause of FQR infections in Australian companion animals was relatively constant between this study and the 5-year-earlier study of Platell et al. (2010) (9/125 isolates, 7.2%). Thus, although the high degree of clonal commonality among FQR clinical isolates from humans vs. companion animals suggests the possibility of bi-directional between-species transmission, the much higher reported prevalence of ST131 and ST1193 among FQR clinical isolates from humans as compared to companion animals suggests that companion animals are spillover hosts rather than being a primary reservoir for these lineages.